Free Intra-Abdominal Air without Peritoneal Perforation after TEM: A Report of Two Cases - Rutger J. Franken; Daan E. Moes; Yair I. Z. Acherman; Eric J. Derksen (Case Reports in Surgery)
Transanal endoscopic microsurgery (TEM) is a minimally invasive treatment modality for a variety of rectal lesions. Due to its minimally invasive nature, TEM has emerged as a safe method. Among most threatening complications are hemorrhage and peritoneal perforation. We report on two patients who demonstrated intra-abdominal free air on an erect chest X-ray after TEM procedure without other findings of a pneumoperitoneum. We hypothesize that due to the combination of elevated pressures in the retroperitoneal cavity and decreased integrity of the retroperitoneal barrier, insufflated CO2 gas can diffuse into the intraperitoneal cavity. Conservative treatment should be considered in patients with free intra-abdominal air postoperatively. However, there should be no suspicion of peritoneal entry during the procedure and the patient should be in generally good condition without severe abdominal symptoms.